Kontribusi Kekuatan Genggaman Tangan Dan Kelentukan Tubuh Terhadap Kemampuan Memanjat Atlet Panjat Tebing Padang Pariaman Kategori Lead - Irfan Saputra; Muhammad Sazeli Rifki (JURNAL STAMINA, 2019)
Research problems in the field that occur in Padang Pariaman rock climbing athletes are the achievements achieved to increase the height are still not optimal and still lack the maximum strength of the muscles of the limbs and arm muscles, especially in the hand that affects fatigue. The aim of this study was to determine the contribution of hand grip strength and flexibility of body towards the climbing ability of Padang Pariaman rock climbing athletes in the lead category.This research uses the correlational method which is intended to determine the contribution of hand grip strength to the climbing ability of Padang Pariaman rock climbing athletes in the lead category. The population in this research were 10 rock climbing athletes of Padang Pariaman Regency. Sampling is done by using total sampling technique. Data collection is carried out by carrying out tests of grip strength, flexibility and climbing ability. The data analysis and hypothesis testing using comparative analysis techniques using different mean test formula (t test) with a significance level α = 0.05.From the data analysis performed, the results obtained: There is a Contribution of Hand Grip Strength ( X1) with Climbing Ability (Y) of Padang Pariaman Rock Climbing Athlete about 85.10%, contribution of Body Flexibility(X2) with Climbing Ability (Y) Padang Pariaman Rock Climbing Athlete amounting to 89.30% and there is a contribution of hand grip strength (X1) and body flexibility (X2) together on climbing ability (Y) Padang Pariaman Rock Climbing Athlete is 76.50%. Keywords: Grip Strength, Flexibility and Climbing Ability [1]Mahasiswa Program Studi Ilmu Keolahragaan untuk wisuda September 2019 2Dosen Jurusan Ilmu Keolahragaan Fakultas Ilmu Keolaragaan Universitas Negeri Padang